Study and evaluation of the performance of Distributed Mobility Management (DMM) for d2d ommunications in SDN-Based LTE networks - سينو, رنيم; رضوان دنده ,; طلال العاتكي , (Latakia University Journal -Engineering Sciences Series, 2023)
With the rapid growth of mobile communication networks and the exponential increase in the number of users of mobile devices, which led to a significant increase in the volume of data traffic and scenarios for connecting to the Internet, due to the continuous demand for multimedia applications in real time, which prompted cellular network operators to introduce communication technology from device to device D2D(Device to Device) in LTE (Long Term Evolution) networks that reduce the traffic of data passing through the base station, but it suffers from some challenges as it depends on a central mobility anchor that manages the movement of users when they are handed over between cells, so In this research, we study and analyze the performance of Distributed Mobility Management (DMM), which is a solution to manage mobility in LTE networks based on Software Defined Networking (SDN), which is a promising approach that supports DMM concepts, because traditional mobility solutions and handover procedures cannot support the continuity of D2D communication. The performance of managing distributed mobility and handovers for D2D connections in an SDN-Based LTE environment was evaluated by several factors, the most important of which are handover failure ratio, packet loss rate and throughput.